Larvicidal activity of Neem oil and three plant essential oils from Senegal against Chrysodeixis chalcites (Esper, 1789) - Saliou Ngom; Raimundo Cabrera Perez; Ma Anta Mbow; Rokhaya Fall; Saliou Niassy; Andreea Cosoveanu; Serigne Mbacké Diop; El Hadji Barka Ndiaye; Moussoukhoye Diop; Georges Lognay (Asian Pacific Journal of Tropical Biomedicine, 2018)
Objective: To evaluate the insecticide, larvicidal and repellent activity of the essential oils from Callistemon viminalis, Melaleuca leucadendron, and Hyptis suaveolens against Chrysodeixis chalcites and to compare it with neem oil (Azadirachta indica). Methods: The essential oils of the leaves of these aromatiques plants were extracted by steam distillation and contacts tests were carried out. Results: Essential oils in ethanol from Callistemon viminalis showed a higher biological activity than the neem with 100% larval mortality at the concentration of 2 μg/mL for 6 h, 100% and 90% in ethanol from Melaleuca leucadendron and Hyptis suaveolens, respectively at the concentration of 4 μg/mL for 24 h. By inhalation, the essential oils from Melaleuca leucadendron and of Hyptis suaveolens were more effective with mortality rates of larvae 100% and 50% respectively at 2 μg/L air applied after 24 h. Nevertheless, the neem has shown to be a repulsive plant and anti-nutritional plant. A significant difference in the percentages of consumption between leaves treated with neem oil and the control samples was observed (Newman-Keuls test) except for Melaleuca leucadendron. Conclusions: The results of the study highlight remarkable biocide, properties of tested extracts, which provides important opportunities for the development of biopesticides.